Cancer cachexia - Misiak, Małgorzata (Contemporary Oncology/Współczesna Onkologia, 2003)
Cancer cachexia occurs in approximately 55–70% of patients with recognised malignancies. The frequency of cancer cachexia does not depend on the histopathologic type of the tumour, being rather related to the primary localisation of the tumour. It is most common in patients with neoplasms of the upper gastrointestinal tract, of the lungs and of the head and neck region. Cancer cachexia may be diagnosed if the patient reports a 10% reduction of body weight during previous 3 months. The clinical symptoms of the cachexia-anorexia syndrome include: weight loss, lack of appetite, rapid hunger fulfilment at meals, weakness, fatigue, apathy, sleep disorders, depression. The syndrome is brought on by a number of pathophysiological mechanisms: – energy “theft” on the part of the tumour, – metabolic balance disorders caused by the accumulation of inflammatory markers – TNF, IL-6 and α- and γ-interferon, – disorders of the physiological mechanisms of food intake by leptin-analogous cytokins. In view of the pathomechanisms leading to cancer cachexia it may be assumed that the syndrome is not caused by malnutrition but is brought on by the malignancy itself. However, malnutrition may aggravate the cachectic symptoms. The treatment of cancer cachexia involves pharmacotherapy and nutrition. At the moment there exist three groups of drugs with proven efficacy: progestagens, corticosteroids and prokinetics. Treatment of cachexia must also involve the treatment of all other aggravating symptoms – pain, depression, mucosal lesions, nausea/vomiting and diarrhoea/constipation.